Cover Picture: Facile Identification of Dual FLT3–Aurora A Inhibitors: A Computer‐Guided Drug Design Approach (ChemMedChem 5/2014). Issue 5 (May 2014) - Chang Hsu, Yung; Ke, Yi‐Yu; Shiao, Hui‐Yi; Lee, Chieh‐Chien; Lin, Wen‐Hsing; Chen, Chun‐Hwa; Yen, Kuei‐Jung; Hsu, John T.‐A.; Chang, Chungming; Hsieh, Hsing‐Pang
<x xml:space="preserve">Abstract</x> The front cover picture shows the in silico design of dual FMS‐like receptor tyrosine kinase‐3 (FLT3) and Aurora kinase A (AURKA) inhibitors—a potential new class of acute myeloid leukemia (AML) therapeutic agents. Computer‐aided drug design (CADD) has various advantages over traditional approaches, such as mitigating laborious optimization work, as well as saving time and being more cost effective. In this work, two consecutive CADD approaches were employed to modify the core structure and side chain of an initial hit compound with AURKA inhibitory activity. A set of virtual compounds derived from the hit structure were designed in silico, and subsequently screened against an FLT3 homology model. The best ranked compounds were then synthesized and evaluated in vitro. Through this approach, a potent, dual FLT3–AURKA inhibitor was generated in a time‐efficient manner. For further details, see the Full Paper by Hui‐Yi Shiao, Hsing‐Pang Hsieh et al. on p. 953 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>